IFN‐γ inhibits basal and α‐MSH‐induced melanogenesis. (25th November 2013) - Son, Jinyoung; Kim, Misun; Jou, Ilo; Park, Kyoung Chan; Kang, Hee Young
Summary Inflammatory cytokines are closely related to pigmentary changes. In this study, the effects of IFN‐γ on melanogenesis were investigated. IFN‐γ inhibits basal and α‐MSH‐induced melanogenesis in B16 melanoma cells and normal human melanocytes. MITF mRNA and protein expressions were significantly inhibited in response to IFN‐γ. IFN‐γ inhibited CREB binding to the MITF promoter but did not affect CREB phosphorylation. Instead, IFN‐γ inhibited the association of CBP and CREB through the increased association between CREB binding protein (CBP) and STAT1. These findings suggest that IFN‐γ inhibits both basal and α‐MSH‐induced melanogenesis by inhibiting MITF expression. The inhibitory action of IFN‐γ in α‐MSH‐induced melanogenesis is likely to be associated with the sequestration of CBP via the association between CBP and STAT1. These data suggest that IFN‐γ plays a role in controlling inflammation‐ or UV‐induced pigmentary changes.